Modelling growth of Norway spruce on former agricultural lands in Latvia - Zvirgzdiņš, Andis (2019)
Adequate growth forecasts are essential for forest management planning. In order to make such forecasts, accurate growth models are required. Due to the rapid growth of Norway spruce (L.) Karst. planted on former agricultural lands, existing growth models are unable to predict the development of Norway spruce with sufficient accuracy. Therefore, the aim of this study was to develop new height development and diameter models for Norway spruce up to 15 years of age. Data used in development of the models was obtained from twelve Norway spruce plantations established on fertile agricultural lands located in eastern Latvia. Height development was modelled using dynamic site equations derived using the generalized algebraic difference approach (GADA). In total fifteen different equations were estimated using non-linear least-square regression. Diameter models were developed using multiple linear regression. Subsequently, further development of the stands was simulated using stand-level management simulation tool StandWise of Heureka-DSS.